(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
In the midst of rapid changes and difficultiesand the tough competition faced by the Iraqi banks, it has become necessary to focus on a significant aspect of administrative work; that is strategic planning and the key role of implementation within this process in improving the banking service quality. It has emerged as a critical and main competitive weapon for distinguishing the services provided by banks from each other in an effort to participate in increasing market share of the bank in question in question; in its growth, continuation and profit increase. The research has addressed the relation between the independent variable (implementation within strategic planning), and the dependent variable (banking service quality and its five sub- variables). The researcher has ended with a set of conclusions; the most important of which is the existence of a significant correlation between the implementation within strategic planning and the variables of banking service quality, except the responsiveness dimension, as the results showed there is no significant correlation between the implementation within strategic planning and Responsiveness dimension within banking services quality. The researcher has also ended with a number of recommendationsincluding the necessity providing qualified and trained employees to implement the strategic planning process, through the engagement of officials involved in implementation process in courses on this field, both inside the